Aluno letrado, professor iletrado digitalmente?: reflexões sobre a docência de inglês em cursos superiores de informática - Fazio, Bernardete Spessoto Rodrigues (2008)
This study aims at describing and interpreting the classroom practice of English teachers who perceive themselves as digitally illiterate while evaluating their university Technology students as digitally literate. By addressing such a phenomenon of lived experience, this investigation therefore aims at reflecting upon teaching practice and digital literacy issues that emerge from instructional contexts in which computers must be used as mediators in ESP classes. To achieve its purpose, this study is founded on the concepts of reflection (Dewey, 1933, 1938, 1967; Perrenoud, 2002; Schön, 1983, 1987, 1992, 2000), digital literacy (Buzato, 2001; Soares, 2002) and English for Specific Purposes (Hutchinson & Waters, 1987; Strevens, 1988; Robinson, 1991; Dudley Evans & St. John, 2000; Ramos, 2005;Celani, 2005). The methodological approach adopted is the hermeneutic-phenomenological one (van Manen, 1990; Ricouer, 1986/2002; Freire, 2006, 2007). The phenomenon description and interpretation emerged from two teachers textual registers (narrative and interview) on their university teaching experiences in Technology courses and on the way they deal with their perceived digital illiteracy in order to fulfill the institutions and learners demands. This research results indicate that searching and reflection are the themes that constitute the phenomenon on focus, thus revealing its nature, its identity. Such outcomes may provide teachers of English with input to reflect upon digital literacy and upon the ESP approach applied to university contexts in which teachers and students have a different level of knowledge and expertise in managing technological resources